Las lecciones de la historia: repensando la política económica del virrey Toledo - Salles, Estela Cristina; Noejovich, Héctor Omar (Economia, 2008)
This paper deals with Viceroy Toledo’s governing plan and the modern concepts of development. It is a review of Viceroy Toledo’s plan genesis from 1568’s Junta Magna, the Toledo’s trip over the Andes and the final establishment of his two main economic policy pillars: the mita and the technological process —using mercury for extracting silver from the ore—.